1997
DOI: 10.1021/jf9609643
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Recent Solventless Methods for the Determination of Procymidone Residues in Wines:  SPME/GC/MS and ELISA Tests

Abstract: Keywords: Procymidone; wine; SPME; ELISA; method comparison

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 22 publications
(20 reference statements)
1
17
0
Order By: Relevance
“…When comparing the concentrations of lambda-cyhalothrin obtained by the SPME procedure with those obtained by the conventional method (Table 5), it was found that results differed only by a factor of 3 for all samples. Similar differences have been reported in the literature, and even with higher ratios when comparing results obtained by SPME with those obtained by conventional methods [29]. Finally, data for lambda-cyhalothrin in real samples followed the expected behavior: the concentration decreased proportionally to time elapsed since active ingredient application (dissipation curve).…”
Section: Analysis Of Real-world Vegetable Samplessupporting
confidence: 87%
See 1 more Smart Citation
“…When comparing the concentrations of lambda-cyhalothrin obtained by the SPME procedure with those obtained by the conventional method (Table 5), it was found that results differed only by a factor of 3 for all samples. Similar differences have been reported in the literature, and even with higher ratios when comparing results obtained by SPME with those obtained by conventional methods [29]. Finally, data for lambda-cyhalothrin in real samples followed the expected behavior: the concentration decreased proportionally to time elapsed since active ingredient application (dissipation curve).…”
Section: Analysis Of Real-world Vegetable Samplessupporting
confidence: 87%
“…Although several papers deal with direct immersion of the SPME fiber into a slurry of fruit with water [21,29], other authors describe the need for a previous extraction of pesticides and the subsequent application of DI-SPME over the separated aqueous extract [30,31,32,33]. The use of microwave-assisted extraction allows one to increase the extraction efficiency of less polar pesticides using water as extractant [29,34]. Once the aqueous extract is obtained, the presence of interfering substances can reduce the efficiency of SPME.…”
Section: Introductionmentioning
confidence: 99%
“…Several kinds of SPME fibers are commercially available including polydimethylsiloxane (PDMS) [5][6][7][8][9][10][11], carbowax-divinlybenzene (CW-DVB) [12,13], polydimethylsiloxane-divinlybenzene (PDMS-DVB) [14][15][16], polyacrylate (PA) [17][18][19], divinylbenzene-carboxen-polydimethylsiloxane (DVB-CAR-PDMS) [20][21][22]. In recent years, studies have been focused on fabricating low cost, simple, robust and long-life fiber for the target analyte [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, the SPE technique is time-consuming, labor-intensive and expensive. Solid phase microextraction (SPME) has been also applied to the determination of fungicides [4][5][6]. Although SPME normally provides a higher selectivity than SPE, the matrix of sample reduces significantly its extraction efficiency [7,8].…”
Section: Introductionmentioning
confidence: 99%